Protecting Florida Horses through Vaccination - Sally DeNotta (EDIS)
Routine vaccination is a critical component of developing a preventative health program for horses. This publication discusses infectious diseases that can be prevented through vaccination and answers questions about equine vaccination. Written by Sally DeNotta, and published by the UF/IFAS Veterinary Medicine—Large Animal Clinical Sciences Department, January 2023.